Caracterização morfológica, molecular e reprodutiva de híbridos interespecíficos de Arachis na busca de resistência a pragas do amendoim - Paula, Ailton Ferreira de (Universidade Federal de São Carlos, 2015)
The peanut (Arachis hypogaea) is, worldwide, an important source of protein and oil. Pests and foliar diseases are among the factors that limit the economically sustainable production of peanuts in Brazil. Among the pests, thrips and the rednecked peanutworm are considered important pests in São Paulo State. To decrease the cost of production on the management of these pests, genetic improvement to obtain resistant varieties from wild plants is a viable alternative. The main obstacle in the genetic improvement is that the vast majority of wild species of Arachis is diploid, while the cultivated species is allotetraploid. For the barrier of ploidy between the wild and the cultivated peanut to be broken, it is necessary to obtain interspecific hybrids genome AB. Such hybrids should be treated with colchicine to induce polyploidy and get fertile hybrids with two distinct complete genomes (amphidiploid), which can be crossed with A. hypogaea to get the same or similar genomic constitution of the cultivated species. The aim of the research were to identify hybrids derived from crosses made between wild species with A, B or K genome that are resistant to thrips and the rednecked peanutworm and hybrids from one amphidiploid and A. hypogaea, characterize the hybrids and their parents 1) by microsatellite molecular markers, 2) by pollen viability and 3) by their morphology. The molecular markers were genotyped in polyacrylamide gel with standard 10 base pairs. The viability of pollen grains was used to analyze the data of analysis of variance and mean Tukey test, and morphological data were analyzed by Principal Component Analysis. Six polymorphic microsatellite loci were analyzed in 25 F1 plants, 18 of them result of selfing and six of hybridization with a total of three different hybrid combinations plus four hybrid plants from across between the amphidiploid An 13 and A. hypogaea. The pollen viability data corroborated the molecular analysis in the identification of hybrids, noting that An 13 had high viability of pollen grains and interspecific hybrids had low values when compared to their parents and selfed individuals of progeny. From the 63 morphological descriptors measured the ones from the main axis expressed the most morphological variation observed. Pollen viability of F1 hybrid plants obtained by cross among A. hypogaea and the amphidiploid An 13 was above 76%, showing the possibility of new interesting genes introgression in A. hypogaea
Morphological, molecular and reproductive characterization of interspecific hybrids of Arachis resistant to pests
Keywords: Genética vegetal; Amendoim; Espécies silvestres; Melhoramento genético; Enneothrips flavens; Stegasta bosquella; Arachis; Wild species; Pre-breeding; CIENCIAS BIOLOGICAS::GENETICA